Strength and conditioning habits of Polish amateur endurance runners - Zbigniew JOST; Maciej CHROBOCZEK (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2024)
Introduction: Correctly performed Strength & Conditioning (S&C) training is important in terms of improving sports performance. This survey was to check S&C habits among amateur runners in Poland. Materials and Methods: The questionnaire dealt with 1) personal and anthropometric data, 2) advancement / fitness level and 3) training habits, which was correctly filled in by 923 people. The participants were matched to five fitness levels (LG1-LG5) depending on sex (W/M) and the selected distance (5K/10K/Half-Marathon). Results: More than half of the respondents (n = 467, 50.6%) considered S&C as very important. The most frequently used S&C activities were uphill runs (n = 608, 65.9%) and bodyweight exercises (n = 596, 64.6%). Some of respondents (n = 418, 45.3% and n = 152, 16.5%) performed resistance training (RT) and plyometric training (PT), respectively. Runners with a higher level of advancement (LG5) performed S&C twice a week (p ≤ 0.05), while athletes from less advanced groups (LG1, LG2) showed a tendency to perform once a week (p = 0.192, p = 0.317), respectively. The respondents also more often chose a low range of repetitions when performing S&C. Conclusions: It is known that the performed S&C should be based on existing scientific evidence. Thus, coaches and practitioners should consider the usefulness of certain activities in the context of implementing them in their athletes' training plans.